Thatcher's troops? Neighbourhood Watch schemes and the search for 'ordinary' Thatcherism in 1980s Britain. Issue 2 (3rd April 2017) - Moores, Chris
Abstract: The spread of Neighbourhood Watch schemes in Britain during the 1980s was remarkable, eventually amounting to 130, 000 schemes covering more than 2.5 million households. Neighbourhood Watch's signs, stickers and high-profile television marketing campaigns made the threat of crime and the need for vigilance a highly visible part of everyday experience across 1980s Britain which can still be seen 30 years later. This article examines the values embodied and transmitted by such initiatives and assesses the anxieties and aspirations of schemes' memberships and those reacting to the schemes assessing the extent to which they were manifestation of an 'ordinary' form of Thatcherism.